The integration of competence model in B2B for sports industry / Yulita Hanum P Iskandar and Noornasirah Nasri - P Iskandar, Yulita Hanum; Nasri, Noornasirah (2014)
This study provides an adopting of business-to-business (B2B) competence model in learning domain for sports industry. Competence provides high quality performance through the tool and helps athletes practice flexible and systematic during training. Competence in B2B has a better option of incomes and profits as an outcome of efficient and effective processes of B2B in a sports industry. Yet ambiguities in the research, including significant uncertainties needed to define the formal associates of competence and B2B. The environment is covered adequately by the cognitive and affective domains. However, in the training situation, the competence is vital. But such work has gone far beyond B2B competence in the context of sportss industry. Cognitive, affective, and psychomotor domains in the literature as being key to B2B in the sports industry, but they also are essential to B2B competence. 56 respondents consisted of all levels of expertise archers. The study completed the pilot study in order to achieve the reliability of the instrument. The proposed model adopts from competence model by and defines the potential and effectiveness usage in a B2B competence for the sports industry. The general conclusion is that the competence domain could be transferable to the business context, as well as considerable amount to learn from excellence in B2B competence.